If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2h-4)(2h-4)=18
We move all terms to the left:
(2h-4)(2h-4)-(18)=0
We multiply parentheses ..
(+4h^2-8h-8h+16)-18=0
We get rid of parentheses
4h^2-8h-8h+16-18=0
We add all the numbers together, and all the variables
4h^2-16h-2=0
a = 4; b = -16; c = -2;
Δ = b2-4ac
Δ = -162-4·4·(-2)
Δ = 288
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{288}=\sqrt{144*2}=\sqrt{144}*\sqrt{2}=12\sqrt{2}$$h_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-12\sqrt{2}}{2*4}=\frac{16-12\sqrt{2}}{8} $$h_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+12\sqrt{2}}{2*4}=\frac{16+12\sqrt{2}}{8} $
| 0.5x−6=x+0.05 | | 6(x+18)=19x | | -1+3b=8(b-2) | | x2+11x-19=0 | | 2^4x+2=5^x | | .21x=56,613,236.65 | | 2+x=7(x+3)-3(2-x) | | -2(x+5)-4=-24 | | 128=-4(-5x+3) | | 3(2n+8)=60 | | 5c+16.5=10c | | -24=2(m+4)+2(4m+4) | | 8x+-2=-42 | | 3x-4+2x-6=20 | | 7b-24=-7(-b+3) | | 5x-4x-3x-2x-1x=87 | | 3(c+5)-2+4c=7(c+2) | | 128=-4(-5x+3)x= | | 1-z=2 | | (x-3)(x+7)=-25 | | Y=10x^2+8x-3 | | 2(x-5)-14=-22 | | 16-x=32 | | x+2x^2=4 | | 5x-15+4x=1 | | 11x=50-9x/10 | | 1x+3=6/2 | | 2(x-5)-14=22 | | 0.667x+6=0.5x+0.25x | | 6(w-5)-3w=+10 | | -2(x-19)=-28 | | n+8/5=7 |